Efektivitas Modul Ajar Kalkulus berbantuan GeoGebra untuk Meningkatkan Hasil Belajar Mahasiswa Teknik Informatika - Dewi Devita; Deby Erdriani; Laila Marhayati (Postgraduate, University of Mataram, 2026)
This study aimed to examine the effectiveness of a GeoGebra-assisted calculus teaching module in improving students’ mathematical learning outcomes. The research employed a One-Group Pretest–Posttest design using a mixed-methods approach. The participants were 17 Informatics Engineering students enrolled in a calculus course at Universitas Putra Indonesia YPTK Padang during the 2025/2026 academic year. Quantitative data were obtained from pretest and posttest scores, while qualitative data were collected through student response questionnaires regarding the use of the teaching module. The quantitative data were analyzed using the Wilcoxon Signed-Rank Test. The results showed a significant improvement in students’ mathematical abilities, with the average score increasing from 58.33 (pretest) to 93.11 (posttest), and the statistical test confirming a significant difference (p = 0.001). Furthermore, the N-Gain analysis indicated an improvement of 83%, which falls into the very effective category based on Hake’s criteria. These findings conclude that the GeoGebra-assisted calculus teaching module is significantly effective in enhancing students’ mathematical abilities and learning outcomes, supporting the implementation of technology-enhanced learning in higher education to promote quality education.